OPPORTUNITIES FOR IMPLEMENTING INTERNАTIONАL METHODS OF СOST САLСULАTION OF RIСE PRODUСTION FOR STRАTEGIС MАNАGEMENT PURPOSES - Khаsаnov, Bаkhodir Аkrаmoviсh; Nurmanov , Karjaubay Tileubayevich; Atamurodov, Saidmurod Yakhyoevich (Antis Publisher, 2025)
Objective: This study aims to explore the feasibility of adopting international methods for calculating the cost of rice production to enhance strategic production management. Method: A qualitative comparative analysis was conducted to examine the differences between traditional domestic costing approaches and internationally recognized standards. The research involved a review of global best practices and frameworks for agricultural cost management, focusing on their adaptability to local conditions. Results: The findings highlight significant discrepancies between existing national methods and international costing practices, particularly in the areas of overhead allocation and cost transparency. By aligning local practices with international standards, rice producers can achieve more accurate cost assessments and make better-informed strategic decisions. Novelty: The study offers an original framework for the transformation of domestic cost calculation systems into globally compatible models, supported by scientific proposals and practical recommendations. This integration contributes to improved cost efficiency, international comparability, and competitiveness in the global agricultural market.